Pengembangan Agraria dan Teknologi Bidang Pertanian: Perspektif Sosiologis-Antropologis - Andria Gustiawan Perangin-angin (Universitas Padjadjaran, 2023)
Agriculture in Indonesia is experiencing uncertainty because of the uneven use of agricultural technology. On the other hand, farmers are trapped in poverty because of limited land ownership, capital and technology. Indonesian farmers do not get certainty concerning crop by-products due to limited land, small production yields due to inadequate technology and very volatile market prices for agricultural production. This study aims to explore the reasons for the delay in the development of the agricultural sector in Indonesia and its relation to agricultural politics. The research method used in this research is descriptive qualitative. This research found that the complexity of agricultural problems that occur in Indonesia is not only due to the lack of development in agricultural technology, but also caused by the lack of agricultural land that can be utilized by farmers